RELASI ANTARA MODAL SOSIAL PENYULUH DAN KEBERHASILAN PENYULUHAN PERTANIAN: Kasus Desa Limbung dan Desa Tubajeng, Kecamatan Bajeng, Kabupaten Gowa, Provinsi Sulawesi Selatan - Muhamad Fathun Munier; M. Saleh S. Ali; Darmawan Salman (Hasanuddin University, 2018)
Agricultural extension is a communication process which is influenced by social capital. This research aims to analyze the relationship of social capital of agricultural extension officers and the success of agricultural extension. This research was conducted in Limbung Village and Tubajeng Village, Bajeng Sub-district, Gowa Regency, South Sulawesi from October to November 2017. The Number of samples in this research were 75 respondents taken from 3 farmer groups namely Farmer Group of Sappaya III, Farmer Group of Taipa Bannya I, and Farmer Group of Bontorita I. Analysis of the data was using pearson product moment correlation analysis on questionnaire with Likert scale. The results showed that the extension programs implemented by extension workers were considered successful by farmers. The social capital of agricultural extension workers assigned to research sites, in the form of trust, reciprocity and social networks is quite high. This is because the farmers assess the performance of extension workers quite well and the farmers are very pleased with the assistance provided especially the provision of information and technology about the farming that they practice. The study also found that social capital in the form of trust, reciprocity, and social network of extension workers partially or collectively affect the success of agriculture extension programs in the three farmer groups studied.